Resolution on the results of the First All-Russian Forum "Therapeutic Education in Endocrinology" - M. V. Shestakova; A. Yu. Mayorov; E. V. Surkova; G. R. Galstyan; A. S. Ametov; M. B. Antsiferov; E. G. Starostina; O. G. Melnikova; L. I. Ibragimova; E. A. Andrianova; E. V. Ershova; I. A. Karpova; et al. (Сахарный диабет, 2022)
According to the decision of the WHO, therapeutic education (TE) of patients is an independent branch of medicine and an essential component of the treatment of chronic diseases, primarily diabetes mellitus and obesity. TE is implemented through the creation of “Schools for patients with diabetes mellitus” and “Schools for patients with overweight” (“Schools”) as a structural unit of a medical institution. On April 25–26, 2022, the First All-Russian Forum «Therapeutic Education in Endocrinology» was held online, organized by the Public Organization «Russian Association of Endocrinologists», which was attended by leading experts in this field. As a result of its work, this Resolution was adopted by the experts. It discusses the methodological and pedagogical foundations of TE, it is proposed to make changes related to the organization of the work of «Schools», tariffing in the obligatory health insurance system, and training of personnel, including nurses.